PENERAPAN APLIKASI DIAGNOSA PENYAKIT JANTUNG MENGGUNAKAN ALGORITMA FORWARD CHAINING BERBASIS MOBILE - Tri Sugihartono; Rendy Rian Chrisna Putra; Dian Ardiansyah (IIB Darmajaya, 2019)
Heart disease ranks the top cause of death compared to stroke, lung cancer, breast cancer, and AIDS. Most ordinary people are very concerned about health, especially heart health. They are reluctant to check their heart health due to lack of service to patients, lack of medical personnel, especially cardiologists and limited working hours of doctors. So the need for a technology that is capable of adopting human thinking is artificial intelligence technology. Expert system is one of the artificial intelligence technologies. This expert system was created as a means to help diagnose and manage patients. The development of this system uses the forward chaining and certainty factor algorithms, and the system development tools used are UML (Unified Modeling Language), this research will produce an expert system application to diagnose heart disease with the output of possible diseases along with the percentage. It is hoped that this expert system will help and accelerate the work of cardiologists in diagnosing early heart disease.Keywords— heart disease, forward chaining, Unified Modeling Language, expert systems, diagnosis